FUNDAMENTAL LESSONS IN THE WORK OF MAHAN: FROM GEOGRAPHICAL DETERMINISM TO THE COMMERCIAL SPIRIT (Journal of the Spanish Institute for Strategic Studies, 2018)
Alfred Mahan is regarded as one of the main exponents of naval strategyin operational and tactical terms. But underlying these considerations,his work contains other important messages about the creation of navalpower that should not be eclipsed by them, beginning with the roleof geography, which, although not decisive when it comes to selectingmajor global powers, can nonetheless play a key role by ruling outcertain states. However, these precepts vouch for a strategist concernedwith issues of a sociological, economic and political nature, whichhe translates into conditions enabling ultimate military success, thusescaping the temptation of determinism.
Keywords: Grand Strategy; geopolitics; markets; national character; public politics